2015
DOI: 10.3390/v8010006
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin as an Antiviral Agent Inhibits Influenza A Virus (IAV) Entry

Abstract: Influenza A viruses (IAVs) cause seasonal pandemics and epidemics with high morbidity and mortality, which calls for effective anti-IAV agents. The glycoprotein hemagglutinin of influenza virus plays a crucial role in the initial stage of virus infection, making it a potential target for anti-influenza therapeutics development. Here we found that quercetin inhibited influenza infection with a wide spectrum of strains, including A/Puerto Rico/8/34 (H1N1), A/FM-1/47/1 (H1N1), and A/Aichi/2/68 (H3N2) with half ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
238
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(256 citation statements)
references
References 50 publications
6
238
0
12
Order By: Relevance
“…Mechanistic investigations revealed that quercetin engages in active interaction with the HA2 subunit. Moreover, it has been established that quercetin is capable of inhibiting the entry of the H5N1 virus using the pseudo virus‐based drug screening system …”
Section: Quercetin Vs Influenza Virus: Modus Operandimentioning
confidence: 99%
“…Mechanistic investigations revealed that quercetin engages in active interaction with the HA2 subunit. Moreover, it has been established that quercetin is capable of inhibiting the entry of the H5N1 virus using the pseudo virus‐based drug screening system …”
Section: Quercetin Vs Influenza Virus: Modus Operandimentioning
confidence: 99%
“…Kinase inhibitors, such as dinaciclib, flavopiridol, SNS-032, and MK2206, and TNF inhibitors, such as etanercept, adalimumab and infliximab, as well as a lipid-lowering simvastatin and antibacterial vancomycin, rifampicin, and erythromycin, were also reported to possess anti-IAV activity [13,104,107,108,116,128,129,147,166,170]. Interestingly, some of the identified inhibitors could be used for treatment of pain and inflammation associated with severe infections [96] (Patent US 20130123345 A1). Our multi-omics studies, however, did not identify some known inhibitors of IAV–host cell interactions, including Mcl1, RNR, Bcl-xL, and Top1 inhibitors [14,171,172].…”
Section: Combination Of Various Omics Techniques Identifies Potentmentioning
confidence: 99%
“…Kinase inhibitors, such as dinaciclib, flavopiridol, SNS-032, and MK2206, and TNF inhibitors, such as etanercept, adalimumab and infliximab, as well as a lipid-lowering simvastatin and antibacterial vancomycin, rifampicin, and erythromycin, were also reported to possess anti-IAV activity [13,104,107,108,116,128,129,147,166,170]. Interestingly, some of the identified inhibitors could be used for treatment of pain and inflammation associated with severe infections [96] (Patent US 20130123345 A1). Our multi-omics studies, however, did not identify some known inhibitors of IAV-host cell interactions, including Mcl1, RNR, Bcl-xL, and Top1 inhibitors [14,171,172].…”
Section: Combination Of Various Omics Techniques Identifies Potentialmentioning
confidence: 99%